2022
DOI: 10.33395/sinkron.v7i1.11263
|View full text |Cite
|
Sign up to set email alerts
|

Development of E-Commerce for Selling Honey Bees in the COVID-19 Era

Abstract: During the Covid-19 pandemic, which has not yet ended, the business of selling honey is a type of business that is able to survive and even increase its market. The trend of selling honey in the era of the Covid-19 pandemic is quite stable and has the potential to be a good source of income because honey can be used as medicine and can increase the body's immunity. Fitorajo Bee Farm is a UMKM engaged in bee cultivation which is located in Pinang City, South Labuhanbatu Regency, North Sumatra Province with orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The system development method used is the waterfall method as illustrated in Figure 1. Waterfall is a software development method that proceeds sequentially and consists of 5 (five) interrelated or influencing stages (Indriani, Dar, & Irmayanti, 2022). The five stages in a row are: Requirement, Design, Implementation, Verification, and Implementation.…”
Section: Methodsmentioning
confidence: 99%
“…The system development method used is the waterfall method as illustrated in Figure 1. Waterfall is a software development method that proceeds sequentially and consists of 5 (five) interrelated or influencing stages (Indriani, Dar, & Irmayanti, 2022). The five stages in a row are: Requirement, Design, Implementation, Verification, and Implementation.…”
Section: Methodsmentioning
confidence: 99%
“…This study applies the System Development Life Cycle with the Waterfall method as a method in developing software because it is easy to implement with a sequential approach (Indriani, Dar, & Irmayanti, 2022). The stages are carried out using the waterfall method as shown in Figure 1 starting from requirements analysis, system design, implementation, and testing (Utami, Zen, & Rauna, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This has an impact on growing demand for honey, and however, at the same time, acacia honey production is lower than the previous year, which has also caused prices to increase. (Indriani et al, 2022), for at least 2 years. During the pandemic, interest in beekeeping increased significantly in anticipation of market demand and sharp increases in honey prices.…”
Section: Pricementioning
confidence: 99%
“…Elsadibah et al, 2023), which is very much needed to prevent transmission and speed up healing. As quoted by Indriani et al (2022), Tempo Magazine reported that online honey sales increased 2 to 3 times during the pandemic. This development of the beekeeping industry in Indonesia is good upstream and downstream.…”
Section: Introductionmentioning
confidence: 97%